2018
DOI: 10.1590/1807-2577.08618
|View full text |Cite
|
Sign up to set email alerts
|

Saúde bucal de idosos com 80 anos ou mais: condição, autopercepção e utilização de serviços odontológicos

Abstract: Resumo Introdução Idosos mais velhos têm saúde bucal precária, procuram pouco os serviços odontológicos e apresentam autopercepção sobre saúde bucal discordante das necessidades de tratamento. Objetivo Comparar a condição e autopercepção de saúde bucal e padrão de utilização de serviços odontológicos de idosos com 80 anos ou mais de um município do sul brasileiro. Método Estudo descritivo com 59 idosos, em 2011 e 2015, no município de Antônio Carlos, Santa Catarina. Foram coletados dados demográficos, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
0
5
0
5
Order By: Relevance
“…Among the clinical changes resulting from the aging process, there is a reduction in taste capacity and changes in the salivary glands. 13 These same authors describe that the taste is altered, as there is a significant decrease in the taste buds in the papillae, especially after seventy years of age. In contrast to the literature, the majority of respondents in this study, who were over 70 years old, reported that with the aging process they do not perceive changes or decreased taste.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Among the clinical changes resulting from the aging process, there is a reduction in taste capacity and changes in the salivary glands. 13 These same authors describe that the taste is altered, as there is a significant decrease in the taste buds in the papillae, especially after seventy years of age. In contrast to the literature, the majority of respondents in this study, who were over 70 years old, reported that with the aging process they do not perceive changes or decreased taste.…”
Section: Resultsmentioning
confidence: 96%
“…In contrast to the literature, the majority of respondents in this study, who were over 70 years old, reported that with the aging process they do not perceive changes or decreased taste. Still, according to the study 13 , the salivary glands undergo an advanced degeneration process with aging, with a functional loss of 20-30%, which causes a reduction in salivary flow and makes saliva more viscous. The results of the literature corroborate this study, in which the majority of the elderly interviewed stated that there is a decrease in saliva and a feeling of dry mouth (xerostomia).…”
Section: Resultsmentioning
confidence: 99%
“…Ferreira, Piuvezam, Werner, & Alves (2006) argue in their study conducted with a low-income population in northeast Brazil that there is a negative perception of oral condition, which is strongly linked to their experience of pain and dental losses. In this context, elderly people aged 80 years or more reported selfperception of dry mouth, difficulties to eat, and seeking less routine dental appointments over the years (Pauli, Figueiredo, Barbosa, Castro, & Mello, 2018). However, this research found a positive representation of oral health, which can be observed in several of the kidney patients' speeches, such as: [...] I think that, in the first place, comes the health of the mouth, because what's the use of having a healthy body, if you don't have oral health, so you'll have your teeth all rotten or no teeth at all, and you'll continue to be sick (CKP 5).…”
Section: Word Cloudmentioning
confidence: 99%
“…Essas situações podem ser amenizadas por meio de intervenções adequadas no estilo de vida, incluindo a adoção de uma alimentação saudável, a prática de atividade física, a cessação do tabagismo, a redução do estresse, entre outras. A má nutrição na idade avançada aumenta o risco de doenças, reduz a funcionalidade, piora a QV e aumenta a mortalidade (ANDRADE et al, 2017;PAULI et al, 2018e KEHOE et al, 2018.…”
Section: Introductionunclassified
“…Além disso, a baixa condição econômica, a capacidade cognitiva e funcional prejudicadas, a depressão e o isolamento, juntamente com os demais fatores que influenciam o consumo alimentar e o estado nutricional dos idosos, contribuem para perda de peso não intencional, desenvolvimento de carências nutricionais ou excesso de peso que irá afetar, de maneira significativa, a saúde e a QV (SILVA e MURA, 2011;ANDRADE et al, 2017;HOLZ et al 2013). Assim, a alimentação e o estado nutricional adequados representam condições essenciais do ser humano e se vinculam diretamente à saúde e a prevenção e reabilitação de agravos, sendo fundamentais para QV e o bem-estar da população idosa (ANDRADE et al, 2017;PAULI et al, 2018;KEHOE et al, 2018;FREITAS et al, 2017).…”
Section: Introductionunclassified